2017
DOI: 10.1177/1350650117718083
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication and frictional analysis of cam–roller follower mechanisms

Abstract: In this work, a full numerical solution to the cam-roller follower-lubricated contact is provided. The general framework of this model is based on a model describing the kinematics, a finite length line contact isothermal-EHL model for the cam-roller contact and a semi-analytical lubrication model for the roller-pin bearing. These models are interlinked via an improved roller-pin friction model. For the numerical study, a cam-roller follower pair, as part of the fuel injection system in Diesel engines, was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 23 publications
(59 reference statements)
1
42
0
Order By: Relevance
“…To avoid dynamic problems in the cam-follower mechanism, the cam profile should be designed carefully for achieving smooth velocity, acceleration and jerk during operation. Alakhramsing et al [17] for example, considered different roller axial profiles in order to study their effects on crucial performance indicators around the nose region. It was found that minimum film thickness and maximum pressure values can be improved significantly, however, at the cost of higher power losses.…”
Section: Cam and Follower Kinematics And Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid dynamic problems in the cam-follower mechanism, the cam profile should be designed carefully for achieving smooth velocity, acceleration and jerk during operation. Alakhramsing et al [17] for example, considered different roller axial profiles in order to study their effects on crucial performance indicators around the nose region. It was found that minimum film thickness and maximum pressure values can be improved significantly, however, at the cost of higher power losses.…”
Section: Cam and Follower Kinematics And Loadingmentioning
confidence: 99%
“…In their study, systematic analyses were presented for the effects of roller crowning and edge geometries in additional to lubricant rheology. More recently, Alakhramsing et al [17][18][19] investigated in detail the contact problem of the cam-follower mechanism in which friction and mixed EHL analyses were considered.…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of completeness, it is worth mentioning some studies on the cam-roller follower mechanisms reported in Alakhramsing et al (2018aAlakhramsing et al ( , 2018bAlakhramsing et al ( , 2019. A full numerical solution of line contact isothermal-EHL model for the cam-roller contact combined with a semi-analytical lubrication model for the roller-pin bearing were used in Alakhramsing et al (2018b). Frictional forces were also evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Convergence is achieved according to user-specified tolerances. For specific numerical details pertaining to the weak finite element formulation of the governing equations and mesh element size distribution, see Habchi et al 23 and Alakhramsing et al 36 as only the main features are recalled here.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…The variation of reduced radius of curvature R, contact force F, and cam surface velocity U c as a function of the cam rotational velocity is depicted in Figure 10(a). The trend of F as a function of cam rotational velocity is extracted from a worst-case scenario mapping of cam rotational speed versus the pumping load on the valve train mechanism (see Alakhramsing et al 36 for more details on this).…”
Section: Parametric Sweep: Variation Of Cam Rotational Speedmentioning
confidence: 99%